Methodological approaches to teaching in practical histology classes. Topic: «Peculiarities of changes in the composition of the organs of the female reproductive system during the ovarian-menstrual cycle. Hormonal regulation of the cycle» - Marchenko , D.G. (Морфологія / Morphologia / Morfologìâ, 2024)
Acquiring knowledge of basic disciplines is an important aspect in the education of students of medical and dental faculties of Dnipro State Medical University. This is the basis for their further mastery of practical skills and abilities at other departments of the institution. The purpose of this work was to analyse the literature sources of domestic and foreign authors in order to form a certain general knowledge base for medical students to better understand this topic. In the course of the literature research, 14 sources of domestic and foreign scientific literature from the electronic databases "PubMed" and textbooks used in the curriculum of medical universities were analysed. Particular attention in this article was paid to the changes that occurred in the structure of the uterine endometrium and at the level of folliculogenesis in the ovaries under the influence of hormones such as estrogens, progesterone, chorionic gonadotropin, luteinising, follicle-stimulating, gonadocrinin and others. These hormones act at different stages of the ovarian-menstrual cycle and lead to certain changes in the structure of the female reproductive system. The study of the organs of the female reproductive system, its hormonal regulation, changes associated with the restructuring of the structure of organs during the ovarian-menstrual cycle is an important aspect of further training in such a clinical department as obstetrics and gynaecology.